做到老 = Live. Work. Die. - Koh, Jinny Jin Hui. (2009)
White hair, creaking joints and lack of stamina – these symptoms are not unfamiliar to the elderly people in Singapore’s greying population. Growing old is a process no one can escape. But how does one ensure he stays employable despite facing these age-related problems?